Effects of Copper and Zinc Supplementation on Weight Gain and Hematological Parameters in Pre-weaning Calves - Mattioli, Guillermo Alberto (2018)
Cow-calf operations may be affected by trace mineral deficiencies, particularly copper (Cu) and zinc (Zn) deficiency, which may decrease the calf daily weight gain and alter hematological parameters. We evaluated the effect of Cu and Zn supplementation on pre-weaning calves (n = 40; 92 ± 6 kg initial body weight) from the Salado River basin, Buenos Aires, Argentina. Calves were divided into four groups (n = 10 each) and subcutaneously administered 0.3 mg/kg Cu (Cu group), 1 mg/kg Zn (Zn group), Cu and Zn together (Cu + Zn group), and sterile saline solution (control group) every 40 days for 120 days. Plasma Cu and Zn concentrations, hematological parameters, and weight were recorded every 40 days. A completely randomized 2 × 2 factorial treatment design was used and data were analyzed with a mixed model for repeated measures over time. Cu and Zn were detected in plasma after the second sampling. Cu × Zn interaction was significant (p = 0.09), being Cu concentration higher in the Cu + Zn than in the Cu group. Differences in weight gain (Zn × time interaction; p   0.1). On the other hand, none of the treatments altered any of the hematological parameters assessed (p > 0.1). Our results show the risk of lower weight gain due to Zn deficiency in pre-weaning calves raised in the Salado River basin.